2012
DOI: 10.1103/physrevb.86.075455
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic growth of N-doped MgO on Mo(001)

Abstract: A simple pathway to grow thin films of N-doped MgO (MgO:N), which has been found experimentally to be a ferromagnetic d 0 insulator, is presented. It relies on the catalytic properties of a Mo(001) substrate using the growth of Mg in a mixed atmosphere of O 2 and N 2 . Scanning tunneling spectroscopy reveals that the films are insulating and exhibit an N-induced state slightly below the conduction band minimum.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 50 publications
4
16
0
Order By: Relevance
“…This agrees with the results of Pesci et al who suggested that the substitutional doping of MgO with N can be realized under oxygen-poor conditions. 26 Here we can conclude that the adsorption of the investigated elements at the O vacancy site becomes more exothermic as the position of the doping element in the PTE approaches that of oxygen. The adsorption of an O atom at an O vacancy site restores perfect MgO(001) and E b (O), in this case, equals À9.37 eV.…”
Section: Structural Electronic and Magnetic Properties Of X-doped (Xmentioning
confidence: 62%
See 1 more Smart Citation
“…This agrees with the results of Pesci et al who suggested that the substitutional doping of MgO with N can be realized under oxygen-poor conditions. 26 Here we can conclude that the adsorption of the investigated elements at the O vacancy site becomes more exothermic as the position of the doping element in the PTE approaches that of oxygen. The adsorption of an O atom at an O vacancy site restores perfect MgO(001) and E b (O), in this case, equals À9.37 eV.…”
Section: Structural Electronic and Magnetic Properties Of X-doped (Xmentioning
confidence: 62%
“…Namely, in ref. 26 the DFT+U approach has been used. The calculated electronic structure of N-MgO(001) also qualitatively agrees with the one given in Ref.…”
Section: Structural Electronic and Magnetic Properties Of X-doped (Xmentioning
confidence: 99%
“…Due to their atomic sizes these dopants are considered as suitable ones for MgO, bulk, surface or nanostructures, in particular, nanotubes addressed here. Namely, these atoms are close to Mg and O in the Periodic [19]. An additional motivation for the present research is very the very promising reactivity of doped MgO(001) surfaces, predicted theoretically [21,22].…”
Section: Introductionmentioning
confidence: 80%
“…[21]. For F and Li, having 2s 2 np 5 [19]. Since F can only receive 1 electron to completely fill its p-shell, the magnetization is now due to an excess charge on the surrounding Mg atoms, amounting to 1 µ B (Fig.…”
Section: Structural Electronic and Magnetic Properties Of Doped Mgomentioning
confidence: 99%
See 1 more Smart Citation